Halal risk analysis in the halal-certified warehousing industry - Mohd Said, Norsabrina (2025)
The halal industry market has witnessed incredible growth and performance not only among the Muslim majority countries but also globally. The increasing global demand for halal-certified products and services has placed significant pressure on the halal supply chain to secure the highest standards of halal integrity, safety, quality, and compliance. While much attention has been directed toward halal supply chain and certification processes, the critical role of halal-certified warehousing and risk analysis remains inadequately addressed in both research and real-life practice. Halal-certified warehousing serves as a key intermediary in preserving the halal status of goods through proper segregation, good hygiene practice, and storage control. However, a series of high-profile incidents that happened in previous years, including the 2011 South African pork and illegal meat mislabeling scandal and the 2020 Malaysian meat cartel case, have revealed serious vulnerabilities of the current Halal supply chain system, including warehousing operations, and highlighting the absence of structured halalspecific risk analysis in warehousing. Thus, this study was conducted based on the qualitative method mainly to identify all the processes involved in halal food warehousing, locate the risks associated with halal food warehousing, and propose a comprehensive Halal risk analysis framework that incorporates Shariah principles and halal risk management practices. The research aims to provide halal industry stakeholders with a practical and comprehensive halal risk analysis framework to enhance compliance, transparency, and trust in halal-certified warehousing operations. Through a systematic review of the literature, regulatory analysis, and industry studies, this study identifies the main core process steps in halal-certified food warehouses are receiving, storing, and delivering. As for the existing risks related to halal, there were in total 47 risks that have been identified by the five selected halal certified food warehouses, including cross-contamination, product mixing, product damage, product documentation difficulties, breakdowns in hygiene and sanitation, inventory discrepancies and etc. All the identified risk were classified into 5 themes based on the result of data analysis; risk during pre-reservation in halal food warehousing, risk during receiving and unloading in halal food warehousing risk during putting away and storage in halal food warehousing, risk during picking in halal food warehousing, and risk during despatch/delivery in halal food warehousing. For ease of reference, each risk event in this study has been labeled with the letter 'R'. The risk analysis results show that only 37 risks ranked 5 to 9 are recognized as halal Control Points in halal-certified food warehouses. The study also mitigated risk responses for the halal control points (HCPs). Last but not least, the findings of this study will contribute to the broader field of halal risk analysis framework in halal food warehousing services by addressing an urgent gap and offering strategic insights for improving halal assurance and sustainability across halal food warehousing activities.